Power to the people: a wiki-governance model for biobanks - Dove, Edward S (BioMed Central, 2012)
Biobanks are adopting various modes of public engagement to close the agency gap between participants and biobank builders. We propose a wiki-governance model for biobanks that harnesses Web 2.0, and which gives citizens the ability to collaborate in biobank governance and policymaking.